A method for identification of isomorphism and structural properties of kinematic chains. (1st January 2011) - Dargar, Ashok; Hasan, Ali; Khan, R.A.
The present work deals with the structural analysis and synthesis of kinematic chains of mechanisms and robot manipulators. Four key problems, detection of isomorphism among kinematic chain, identification of isomorphism among inversions of given kinematic chain, identification of rigid sub-chain and type of degree of freedom of kinematic chains are considered. A method based on the flow path matrices of kinematic chains is proposed and two new structural invariants, sum of the absolute values of the characteristic polynomial coefficients (SCPC) and maximum absolute value of the characteristic polynomial coefficient (MCPC) are determined using software MATLAB. These invariants are used as the composite identification number of a kinematic chain and mechanisms. The advantage of this method is that it covers all planar kinematic chains of one, two and three degree of freedom at once for identification of isomorphism and for structural properties.